Logging Output Relative to Tree Dimensions in the Tropical Hardwood Forests of Kerala (India) - Nair, N. R. (Indian Forester, 1977)
This paper deals with a study on the relation between logging output and tree and log dimensions, such as G.B.H. and mid-girth. The results of this study show that: within the dimensional range of trees and logs covered by the study, (i) Changes in the size of trees do not cause any significant change in the output for the work of felling trees. (ii) Output for the work of debarking, in terms of the volume of timber produced, increases with the increase in the girth of the logs. (iii) The work of cross-cutting and shaping of log has a maximum output at an optimum tree size. The works of felling trees cross-cutting, shapping and debarking of logs, when taken together, also show the above trend.